Late prehistoric settlement, Berryhill, Aberdeenshire - Murray, Hilary; Saville, A (Proceedings of the Society of Antiquaries of Scotland, 2003)
Excavation in 1999 and 2000 revealed occupation evidence dating from the Neolithic to the twentieth century. A hilltop stone walled enclosure possibly from the first century AD and a contemporaneous stone hut circle, taken along with the later rectangular structures, together urge caution in interpretation of apparently simple hilltop sites.